Photobleaching effect in azo-dye containing epoxy resin films: The potentiality of carbon nanotubes as azo-dye dispensers - Díaz Costanzo, Guadalupe (2015)
Azo-dye molecules may suffer from bleaching under certain illumination conditions. When this photoinduced process occurs, it generates an irreversible effect that is characterized by the loss of absorption of the dye molecule. Moreover, the well-known isomerization of azodye molecules does not occur anymore. In this work it is shown how the addition of a small amount of multi-walled carbon nanotubes (MWCNTs) helps to decrease the bleaching effect in a photosensitive guest-host azo-polymer film. Two different systems were fabricated using an epoxy resin as polymer matrix. An azo-dye, Disperse Orange 3, was used as photosensitive material in both systems and MWCNTs were added into one of them. The optical response of the polymeric systems was studied considering the degree of photoinduced birefringence. Photobleaching of the azo-dye was observed in all cases however, the effect is lower for the composite material containing 0.2 wt % MWCNTs. The weak interaction between MWCNTs and dye molecules is less favorable when the material is heated. The optical behavior of the heated composite material suggests that carbon nanotubes can be potentially used as azo dye dispensers. The results are interpreted in terms of the non-covalent interaction between azo-dye molecules and MWCNTs.